2020
DOI: 10.14569/ijacsa.2020.0110156
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Brain Magnetic Resonance Images Tumor Detection and Classification Techniques

Abstract: The image segmentation, tumor detection and extraction of tumor area from brain MR images are the main concern but time-consuming and tedious task performed by clinical experts or radiologist, while the accuracy relies on their experiences only. So, to overcome these limitations, the usage of computer-aided design (CAD) technology has become very important. Magnetic resonance imaging (MRI) and Computed Tomography (CT) are the two major imaging modalities that are used for brain tumor detection. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Therefore, it has become crucial to use CAD technology. The two primary imaging modalities used to detect brain tumors are MRI and CT [26]. A study suggested a way to detect and diagnose lung nodules as soon as feasible in order to treat them successfully and lessen the burden on patients and the healthcare system.…”
Section: -2022mentioning
confidence: 99%
“…Therefore, it has become crucial to use CAD technology. The two primary imaging modalities used to detect brain tumors are MRI and CT [26]. A study suggested a way to detect and diagnose lung nodules as soon as feasible in order to treat them successfully and lessen the burden on patients and the healthcare system.…”
Section: -2022mentioning
confidence: 99%
“…Ullah et al [7] conducted a rigorous analysis of the various image processing methods for brain tumor detection. There are many pre-processing techniques used like denoising, skull stripping, and intensity normalization.…”
Section: Literature Surveymentioning
confidence: 99%
“…The goal of this image processing is always to determine tumor location [28]. The main concern of segmentation, detection, and extraction of tumor area from imaging modalities images that helps to perform radiologists or clinical experts for treatment planning [29].…”
Section: Tumor Localizationmentioning
confidence: 99%